Methodological approaches for inducing diabetes-like metabolic conditions in zebrafish larvae - Kurach, Lukasz (Current Issues in Pharmacy and Medical Sciences, 2025)
Zebrafish represent a widely used model for studying metabolic disorders due to their genetic similarity to humans, low cost of breeding and suitability for high-throughput screening. This review presents current methodological approaches for inducing diabetes-like metabolic conditions in zebrafish larvae, focusing on both glucose-based exposure (immersion in high-glucose solutions) and chemical induction methods using compounds such as streptozotocin and alloxan. The main advantages and limitations of each protocol are summarized, including variations in exposure duration, developmental stage and compound concentration. Standardized and validated protocols remain crucial for enhancing comparability across studies and for enabling reliable preclinical testing of antidiabetic compounds. The zebrafish larval model continues to offer a promising and flexible system for investigating the mechanisms underlying diabetes and related metabolic dysfunctions.